Unsaturated hydrocarbons adsorbed on low coordinated Pd surface: A periodic DFT study - Belelli, Patricia Gabriela (2010)
In this work, the adsorption of several unsaturated hydrocarbon molecules on a stepped Pd(4 2 2) surface was studied. Using a periodic method based on the Density Functional Theory (DFT) formalism, different adsorption geometries for ethylene, three butene isomers (cis/trans-2-butene and 1-butene), acetylene and 2-butyne were investigated. The results were compared with those obtained for a free defect surface as Pd(1 1 1). The 1-butene is more stable on the free defect surface than on Pd(4 2 2). On the stepped surface, the olefins adsorb tilted towards the step and increases, in almost all the cases, the magnitude of the adsorption energy. Conversely, the 3-fold site is the most stable for the alkynes adsorption on the stepped surface, as it was found on Pd(1 1 1). The analysis of the dipole moment change indicate a charge transfer from the double bond of the olefin to the metallic surface, being higher for the Pd(1 1 1) surface. In case of the alkynes, an important back-donation is produced. Except the alkynes and the 1-butene molecule, the results show the preference of ethylene and cis/trans-2-butene to be adsorbed on the stepped surface. These observations are related with experimental catalytic results. © 2009 Elsevier B.V. All rights reserved.